Descemet's Membrane Detachment : An Evidence of Old Ocular Trauma - Babitha Valiyaveettil; Sanaa Mohammed Konnakkodan; Arun Kumar (Delhi Journal of Ophthalmology)
A 60 year old female presented with defective vision both eyes and on examination was found to have a nebular corneal opacity in right eye which on evaluation was found to be a descemet's membrane detachment which developed post an episode of trauma to right eye she sustained 25 years back and which was forgotten till then. A diagnosis of old descemet membrane detachment was made. In view of the long duration before presentation and since the central visual axis was clear it was decided to manage the DMD conservatively without surgical intervention.